PERANCANGAN STRATEGI KREATIF BRAND ATTRIBUTES PADA KEBUN STROBERI DESA LEBAKMUNCANG BERSAMA ULTRA MILK DALAM MENINGKATKAN RECOGNITION TERHADAP KELUARGA MUDA - Octavia Muslimah, Vani; Syafikarani, Aisyi; Agung, I Gusti (eProceedings of Art & Design, 2024)
The phenomenon of rebound travel, or the increase in tourist visits, is once againoccurring in Indonesia's tourism industry, driven by technological advancements such as online travel platforms and promotions on social media that facilitate travel processesand change tourist behavior. Based on data from the Ministry of Tourism and Creative Economy (Kemenparekraf), there was a 12.5% increase in domestic tourist visits in thefirst semester of 2023 compared to the previous year (Puspita, 2023). This increase has a positive impact on regional economic growth, creating new livelihood opportunities forresidents. This design focuses on the brand attributes for the Strawberry Farm in Lebakmuncang Village, which has experienced a decline in tourist numbers despite itsvarious tourism potentials. The methods used include interviews, observations, and secondary data analysis to gather information on the existing potentials and challenges.The design results indicate that the village needs to enhance its branding and promotion to increase tourism appeal. The proposed strategy includes marketing through socialmedia and collaboration with a national brand, Ultra Milk, to expand market reach and increase recognition. Suggestions for future research include conducting a more in-depthstudy on the effectiveness of the proposed marketing strategies and their impact on the local community's welfare. For Lebakmuncang Village, it is recommended to continuedeveloping strawberry product innovations and enhancing promotional efforts through various social media platforms and collaborations with travel agencies to expand market reach. Keywords: Lebakmuncang, strawberry farm, brand attributes.